PROFESSIONALISM AND THE ROLE OF SHADOW TEACHERS IN INCLUSIVE EDUCATION SERVICES AT BUTTERFLY LEARNING CENTER - Inayatul Lathifah; Joko Pamungkas (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to describe the professionalism and roles of shadow teachers in supporting inclusive education services at Butterfly Learning Center (BLC). As an institution dedicated to transitioning children with special needs (CSN) into formal schooling, BLC implements an intensive one-to-one accompaniment system. This study employed a descriptive qualitative method, with data collected through in-depth interviews, direct observation of accompaniment activities, and document review. The findings indicate that shadow teachers at BLC fulfill multifunctional roles, including identifying each child's specific needs, designing intervention programmes, developing basic independence skills, and providing evaluations and progress reports to parents and classroom teachers. The professionalism of shadow teachers is demonstrated through their ability to adapt instructional strategies in accordance with each child's concentration level, as well as their physical and cognitive limitations. Furthermore, teachers engage in ongoing collaboration with parents to monitor and evaluate children's progress through regular daily reports. This study concludes that the competence and dedication of shadow teachers are critical factors in the successful transition of children with special needs into broader educational settings. An effective shadow teacher does not only focus on academic readiness, but also place equal emphasis on developing independence as a necessary foundation for children's social integration in the future.